COMPARISON OF FOOD WASTE, PONGAMIA SEED COATS AND COMMERCIAL ACTIVATED CARBON AS EFFECTIVE ADSORBENTS IN DAIRY EFFLUENT TREATMENT - DAWN SS,; N, Nirmala; RASHMI KUMARI, (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  Activated carbons are widely used as adsorbents for the removal of organic chemicals and metal ions of environmental or economic concern from air, gases, potable water and wastewater. Dairy industry is one of the major agro-based industries, which involves processing of raw milk to consumer products. The objective of the present work is to synthesize and characterize activated carbon adsorbents from the selected raw materials, through pyrolysis assisted by chemical activation, for odor removal by adsorption of organic matter from dairy waste water. For this purpose, Pongamia seeds and food waste were selected as precursor materials. Commercial charcoal was also used as a reference adsorbent. The carbon produced by pyrolysis of Pongamia seeds and food waste are chemically activated with various activating agents, namely zinc chloride and potassium hydroxide. Characterization tests were carried out for the activated carbon as well as for the effluent sample. Adsorption studies of the dairy effluent samples were carried out using the prepared activated carbon for biological oxygen demand and chemical oxygen demand control. Activated carbon prepared from food waste activated by zinc chloride and Pongamia seed coats activated by potassium hydroxide having lower density, higher volatile matter content, lower ash content and lower moisture content showed favourable characterization results in comparison with commercial grade activated carbon. Hence, it is concluded that activated adsorbents synthesized from food waste and Pongamia seed coats can be considered as effective replacements for commercial activated carbon for dairy waste treatment as they are also cost-effective and environment friendly. Keywords: Dairy waste water, Chemical oxygen demand, Biological oxygen demand, Food waste, Pongamia pinnata, Activated carbon, Adsorption, Odour removal.